Dual anti-platelet therapy following percutaneous coronary intervention in a population of patients with thrombocytopenia at baseline: a meta-analysis - Manyun Long; Ziliang Ye; Jing Zheng; Wuxian Chen; Lang Li (BMC, 2020)
Abstract Background In this meta-analysis, we aimed to systematically compare the post percutaneous coronary interventional (PCI) adverse bleeding events, stent thrombosis, stroke and other cardiovascular outcomes in a population of patients with and without thrombocytopenia at baseline who were followed up on dual antiplatelet therapy (DAPT). Methods Relevant English language articles which were published before June 2019 were retrieved from MEDLINE, http://www.ClinicalTrials.com , EMBASE, Cochrane central, and Google scholar briefly using specific terms such as percutaneous coronary intervention or dual antiplatelet therapy, and thrombocytopenia. All the participants were followed up on DAPT following discharge. Specific endpoints including bleeding events, stent thrombosis, stroke and other adverse cardiovascular events were assessed. The latest version of the RevMan software was used for the statistical assessment. Odd ratios (OR) with 95% confidence intervals (CI) based on a fixed or a random statistical model were used to represent the data graphically. Results A total number of 118,945 participants (from 8 studies) were included with 37,753 suffering from thrombocytopenia at baseline. Our results showed post procedural bleeding (OR: 1.89, 95% CI: 1.16-3.07; P = 0.01), access site bleeding (OR: 1.66, 95% CI: 1.15-2.39; P = 0.006), intra-cranial bleeding (OR: 1.78, 95% CI: 1.30-2.43; P = 0.0003), gastro-intestinal bleeding (OR: 1.44, 95% CI: 1.14-1.82; P = 0.002) and any major bleeding (OR: 1.67, 95% CI: 1.42-1.97; P = 0.00001) to be significantly higher in thrombocytopenic patients treated with DAPT after PCI. Total stroke (OR: 1.45, 95% CI: 1.18-1.78; P = 0.0004) specifically hemorrhagic stroke (OR: 1.67, 95% CI: 1.30-2.14; P = 0.0001) was also significantly higher in these patients with thrombocytopenia at baseline. All-cause mortality and major adverse cardiac events were also significantly higher. However, overall total stent thrombosis (OR: 1.18, 95% CI: 0.90-1.55; P = 0.24) including definite and probable stent thrombosis were not significantly different compared to the control group. Conclusions According to the results of this analysis, DAPT might have to be cautiously be used following PCI in a population of patients with thrombocytopenia at baseline due to the significantly higher bleeding rate including gastro-intestinal, intra-cranial bleeding and hemorrhagic stroke. Hence, special care might have to be taken when considering anti-platelet agents following PCI in these high risk patients. However, considering the present limitations of this analysis, this hypothesis will have to be confirmed in future trials.